18F-DCFPyL (PSMA) PET as a radiotherapy response assessment tool in metastatic prostate cancer. (March 2023) - Mesci, Aruz; Ahmadi, Elham; Ali, Amr; Gouran-Savadkoohi, Mohammad; Evelyn Tsakiridis, Evangelia; Biziotis, Olga-Demetra; Chow, Tom; Kapoor, Anil; Sur, Monalisa; Steinberg, Gregory R.; Liu, Stanley; Zukotynski, Katherine; et al.
Highlights: With PSMA-PET we observed high rates of metastatic PrCa response to RT. The regulation of PSMA expression by RT remains unclear. We found that PSMA expression in PrCa tumors is highly heterogeneous. Loss of PSMA expression was observed in human PrCa models surviving high-dose RT. This work suggests cautious interpretation of PSMA-PET results in irradiated metastatic sites and need for further studies. Abstract: Background: Prostate Specific Membrane Antigen (PSMA) – positron emission tomography (PET) guides metastasis-directed radiotherapy (MDRT) in prostate cancer (PrCa). However, its value as a treatment response assessment tool after MDRT remains unclear. Importantly, there is limited understanding of the potential of radiotherapy (RT) to alter PSMA gene (folate hydrolase 1; FOLH1) expression. Methodology: We reviewed a series of 11 men with oligo-metastatic PrCa (25 metastasis sites) treated with MDRT before re-staging with 18 F-DCFPyL (PSMA) PET upon secondary recurrence. Acute effects of RT on PSMA protein and mRNA levels were examined with qPCR and immunoblotting in human wild-type androgen-sensitive (LNCap), castrate-resistant (22RV1) and castrate-resistant neuroendocrine (PC3 and DU145) PrCa cell lines. Xenograft tumors were analyzed with immunohistochemistry. Further, we examined PSMA expression in untreated and irradiated radio-resistant (RR) 22RV1 (22RV1-RR) and DU145 (DU145-RR) cells and xenografts selected for survival after high-dose RT. Results: The majority of MDRT-treated lesions showed lack of PSMA-PET/CT avidity, suggesting treatment response even after low biological effective dose (BED) MDRT. We observed similar high degree of heterogeneity of PSMA expression in both human specimens and in xenograft tumors. PSMA was highly expressed in LNCap and 22RV1 cells and tumors but not in the neuroendocrine PC3 and DU145 models. Single fraction RT caused detectable reduction in PSMA protein but not in mRNA levels in LNCap cells and did not significantly alter PSMA protein or mRNA levels in tissue culture or xenografts of the other cell lines. However, radio-resistant 22RV1-RR cells and tumors demonstrated marked decrease of PSMA transcript and protein expression over their parental counterparts. Conclusions: PSMA-PET may be a promising tool to assess RT response in oligo-metastatic PrCa. However, future systematic investigation of this concept should recognize the high degree of heterogeneity of PSMA expression within prostate tumors and the risk for loss of PSMA expression in tumor surviving curative courses of RT.